Factors associated with a prolonged hospital stay during induction chemotherapy in newly diagnosed high risk pediatric acute lymphoblastic leukemia. (August 2018) - Warrick, Kasper; Althouse, Sandra K.; Rahrig, April; Rupenthal, Joy; Batra, Sandeep
Highlights: High risk ALL patients experience significant adverse events during induction. Factors predictive of prolonged hospital stay during induction were identified. Outpatient management of new ALL patients is often not feasible or safe. An aggressive and close outpatient follow up of these patients is indicated. Abstract: Background: High Risk (HR) or Very High Risk (VHR) acute lymphoblastic leukemia (ALL) treated with 4 drug induction chemotherapy is often associated with adverse events. The aim of this study was to identify risk factors associated with a prolonged inpatient length of stay LOS during induction chemotherapy. Procedure: Data from patients (N = 73) (age<21 years) was collected through a retrospective chart review. Univariable and multivariable logistic regression was used to test for statistical significance. The overall survival and disease (leukemia)-free survival were analyzed using the Kaplan–Meier method and log-rank test. Results: Of the 73 patients, 42 (57%) patients were discharged on day 4 of induction (short LOS, group A), while 31 (43%) patients (group B) experienced a prolonged LOS or an ICU stay (16 ± 27.7 days, median hospital stay = 8 days vs 4 days (group A), p = 0.02) due to organ dysfunction, infectious or metabolic complications. Group B patients were more likely to have a lower platelet count, serum bicarbonate, and a higher blood urea nitrogen (BUN) on day 4 of treatment (OR = 4.52, 8.21, and 3.02, respectively, p < 0.05). Multivariable analysis identified low serum bicarbonate (p = 0.002) and a platelet count<20, 000/μL (p = 0.02) on day 4 of induction to be predictive of a prolonged LOS. Twenty six (group A (n = 16, 36%) and B (n = 11, 35%), p = 0.8) patients experienced unplanned admissions, within 30 days of discharge. Conclusions: A significant proportion of newly diagnosed HR or VHR pediatric ALL patients experience a prolonged LOS and unplanned re-admissions. Aggressive discharge planning and close follow up is indicated in this cohort of patients.